Bionic Engineered Protein Coating Boosting Anti‐Biofouling in Complex Biological Fluids. Issue 6 (19th December 2022) - Zhao, Ziqian; Pan, Mingfei; Qiao, Chenyu; Xiang, Li; Liu, Xiong; Yang, Wenshuai; Chen, Xing‐Zhen; Zeng, Hongbo
Abstract: Implantable medical devices have been widely applied in diagnostics, therapeutics, organ restoration, and other biomedical areas, but often suffer from dysfunction and infections due to irreversible biofouling. Inspired by the self‐defensive "vine‐thorn" structure of climbing thorny plants, a zwitterion‐conjugated protein is engineered via grafting sulfobetaine methacrylate (SBMA) segments on native bovine serum albumin (BSA) protein molecules for surface coating and antifouling applications in complex biological fluids. Unlike traditional synthetic polymers of which the coating operation requires arduous surface pretreatments, the engineered protein BSA@PSBMA (PolySBMA conjugated BSA) can achieve facile and surface‐independent coating on various substrates through a simple dipping/spraying method. Interfacial molecular force measurements and adsorption tests demonstrate that the substrate‐foulant attraction is significantly suppressed due to strong interfacial hydration and steric repulsion of the bionic structure of BSA@PSBMA, enabling coating surfaces to exhibit superior resistance to biofouling for a broad spectrum of species including proteins, metabolites, cells, and biofluids under various biological conditions. This work provides an innovative paradigm of using native proteins to generate engineered proteins with extraordinary antifouling capability and desired surface properties for bioengineering applications. Abstract : A novel engineered BSA@PSBMA protein (bovine serum albumin, BSA and poly(sulfobetaine methacrylate), PSBMA) is developed for surface‐independent coating and to remove the intrinsic limitation of native proteins as antifouling coatings in complex biological environments. High‐efficient resistance to various biofoulants in complex conditions is achieved through using a bionic "vine‐thorn" design to tune the interfacial interactions at the molecular scale.